Pelatihan Software Autocad Sebagai Penunjang Mata Kuliah Menggambar Teknik - Arif Rakhman Suharso; Wahyu Ari Putranto; Susanto Susanto; Marina Artiyasa (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Mastery of AutoCAD software for engineering students is very necessary to assist in technical drawing. Training using AutoCAD software for engineering students at Nusa Putra University can help them to better understand design in both 2-dimensional and 3-dimensional drawing using AutoCAD software. The training was carried out in 3 sessions, namely a theoretical presentation session by the resource person, followed by a drawing practicum which was attended by students using computers in the Nusa Putra University engineering laboratory, the last was a question and answer session. This activity received a positive response from students and lecturers so it needs to be held every year.